Physical drivers of sediment-water interaction on the Beaufort Sea shelf. (March 2022) - Dabrowski, Jessica S.; Pickart, Robert S.; Stockwell, Dean A.; Lin, Peigen; Charette, Matthew A.
Abstract: Climate change is causing sea ice loss on Arctic continental shelves, resulting in increases of shelf-derived materials to the Arctic Ocean. Sediment-water interaction can chemically transform water as it moves across the shelf, enriching shelf waters in nutrients and carbon, which can impact primary productivity and greenhouse gas cycling. However, the drivers of sediment-water interaction in the Arctic Ocean are poorly understood. In this study, we use radium isotope measurements and physical data from a cruise to the Beaufort shelf in late-October-November 2018 to investigate the impact of storm events and winter water formation on sediment-water interaction. In response to winter water formation, radium-228 and 228 Ra/ 226 Ra increased in shelf bottom waters, with both indicative of enhanced sediment-water exchange. Ammonium, an important nutrient for phytoplankton growth with a known sediment source, also increased during this time period. Our results suggest that processes related to ice formation, together with wind effects, have the ability to drive dissolved constituents from sediment porewaters into the water column. The spatial variability in chemical constituents and water mass ages based on short-lived Ra isotopes suggest that these sediment-water interaction events are episodic in nature, and that storm-driven mesoscale water column features can drive local exchange with the benthos. Highlights: Sediment-water exchange processes are observed with winter water formation. Storm events can also drive local exchange with the benthos. Winter water formation can lead to inputs of nutrients essential for phytoplankton.